Dismantling Green Colonialism Energy and Climate Justice in the Arab Regio - Hamouchene, Hamza (Pluto Press, 2023)
A thought-provoking book which empowers its readers to think about the problems in systematic, transformative ways' - Fadhel Kaboub, President of the Global Institute for Sustainable Prosperity The Arab region is a focus of world politics, with authoritarian regimes, significant fossil fuel reserves and histories of colonialism and imperialism. It is also the site of potentially immense green energy resources. The writers in this collection explore a region ripe for energy transition, but held back by resource-grabbing and neocolonial agendas. They show the importance of fighting for a just energy transition and climate justice - exposing policies and practices that protect global and local political elites, multinational corporations and military regimes. Covering a wide range of countries from Morocco, Algeria and Tunisia to Egypt, Sudan, UAE, Saudi Arabia, Jordan and Palestine, this book challenges Eurocentrism and highlights instead a class-conscious approach to climate justice that is necessary for our survival.